Physiological and Molecular Characterization of Hydroxyphenylpyruvate Dioxygenase (HPPD)-inhibitor Resistance in Palmer Amaranth (Amaranthus palmeri S.Wats.) - Nakka, Sridevi; Godar, Amar S.; Wani, Prashant S.; Thompson, Curtis R.; Peterson, Dallas E.; Roelofs, Jeroen; Jugulam, Mithila (Frontiers in Plant Science, 2017)
Herbicides that inhibit hydroxyphenylpyruvate dioxygenase (HPPD) such as mesotrione are widely used to control a broad spectrum of weeds in agriculture. Amaranthus palmeri is an economically troublesome weed throughout the United States (US). The first case of evolution of resistance to HPPD-inhibiting herbicides in A. palmeri was documented in Kansas (KS) and later in Nebraska (NE). The objective of this study was to investigate the mechansim of HPPD-inhibitor (mesotrione) resistance in A. palmeri. Dose response analysis revealed that this population (KSR) was 10-18 times more resistant than their sensitive counterparts (MSS or KSS). Absorbtion and translocation analysis of [14C] mesotrione suggested that these mechanisms were not involved in the resistance in A. palmeri. Importantly, mesotrione (>90%) was detoxified markedly faster in the resistant populations (KSR and NER), within 24 hours after treatment (HAT) compared to sensitive plants (MSS, KSS, or NER) . However, at 48 HAT all populations metabolized the mesotrione, suggesting additional factors may contribute to this resistance. Further evaluation of mesotrione-resistant A. palmeri did not reveal any specific resistance-conferring mutations nor amplification of HPPD gene, the molecular target of mesotrione. However, the resistant populations showed 4-12 fold increase in HPPD gene expression. This increase in HPPD transcript levels was accompanied by increased HPPD protein expression. The significant aspects of this research include: the mesotrione resistance in A. palmeri is conferred primarily by rapid detoxification (non-target-site based) of mesotrione; additionally, increased HPPD gene expression (target-site based) also contributes to the resistance mechanism in the evolution of herbicide resistance in this naturally occurring weed species.